Zaupanje in ekonomska uspešnost - Rus, Andrej (Teorija in praksa, 2008)
The paper is concerned with the central question found in the ever growing literature on trust, namely, what is the effect of trust on economic performance and what are the causal mechanisms through which trust affects performance. In the first part, we consider the problem of trust and show that it is important to distinguish between three rather than two types of trust. The typology includes not only institutional and interpersonal trust but also network trust. In the second part of the paper, we analyse the causal mechanisms that are in place when each type of trust affects performance. We demonstrate that each type of trust affects performance by employing a different causal mechanism. Interpersonal trust leads to increased performance by encouraging co-operation among actors. Network trust improves performance by enabling co-ordination among actors. Institutional trust exerts a positive influence by facilitating the participation of actors in economic transactions. Distinctions between the types of trust and the mechanisms though which they affect performance are not only essential for understanding the relationship between trust and performance but also for formulating better policies for economic development.
Keywords: Trust; Zaupanje; Economic successfulness; Ekonomska uspešnost; Cooperation; Sodelovanje; Coordination; Koordinacija; Participacija; Participation; podjetje; corporation; uspešnost poslovanja